CREATION OF AN ELECTRONIC PRACTICE TEXTBOOK ON GRAMMAR BASED ON THE ENTERPRISE-3 - Данилова, В.В.; Исмаилова, А.А. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2015)
The given article is devoted to creation of an electronic practice textbook on grammar based on the Enterprise-3.The authors identifyprinciples, methods, deductive and inductive approaches to teaching grammar, use of electronic textbooks in school, main stages of creation of the electronic practice textbook, the system of exercises with the regional component of the grammar from the textbook Enterprise-3.Practical value of the research consists in the elaborated electronic practice textbook on grammar with regional component based on the Enterprise-3.
Keywords: electronic practice textbook; teaching English grammar; regional component; Enterprise -3; the system of exercises